Ethnic tourism in Singapore - Ng, Say Kai (2011)
This report explores the ever-present conflict between cultural heritage and commercialised tourism in Singapore’s context. This is especially relevant due to the introduction of manmade attractions in recent years, such as the Singapore Flyer and the Integrated Resorts (IRs). A survey was conducted to gather tourists’ opinions on the cultural heritage tourism scene, specifically ethnic tourism, in Singapore. The findings indicated that culture-related attractions have a substantial appeal in Singapore, despite respondents giving a relatively low attractiveness rating for “Culture & History” as an aspect of Singapore. In fact, tourists are more likely to enjoy visits to culture-related attractions compared to those classified as “Fun and Entertainment”. In addition, respondents were asked to elaborate on their experiences and perspectives on authenticity of the ethnic districts of Singapore, namely Chinatown, Little India and Kampong Glam. Some differences were noted among the three ethnic districts, such as a perceived higher overall authenticity for Little India compared to Chinatown and Kampong Glam. This study thus contributes to the understanding of cultural heritage (ethnic heritage) as a form of sustainable tourism in Singapore.